Exploring the central region of NGC 1365 in the ultraviolet domain - Kurian, Kshama Sara; Stalin, C. S.; Wylezalek, Dominika; Lyubenova, Mariya; Adhikari, Tek Prasad; Devaraj, Ashish; Sagar, Ram; Kissler-Patig, Markus; Mondal, Santanu (The astrophysical journal, 2024)
Active galactic nuclei (AGN) feedback and its impact on their host galaxies are critical to our understanding of galaxy evolution. Here, we present a combined analysis of new high resolution ultraviolet (UV) data from the Ultraviolet Imaging Telescope (UVIT) on AstroSat and archival optical spectroscopic data from the Very Large Telescope/MUSE, for the Seyfert galaxy, NGC 1365. Concentrating on the central 5 kpc region, the UVIT images in the far- and near-UV show bright star-forming knots in the circumnuclear ring as well as a faint central source. After correcting for extinction, we found the star formation rate (SFR) surface density of the circumnuclear 2 kpc ring to be similar to other starbursts, despite the presence of an AGN outflow, as seen in [O iii] 5007 Å. On the other hand, we found fainter UV and thus lower SFR in the direction southeast of the AGN relative to northwest in agreement with observations at other wavelengths from JWST and Atacama Large Millimeter/submillimeter Array. The AGN outflow velocity is found to be lesser than the escape velocity, suggesting that the outflowing gas will rain back into the galaxy. The deep UV data have also revealed diffuse UV emission in the direction of the AGN outflow. By combining [O iii] and UV data, we found the diffuse emission to be of AGN origin.
Gesehen am 17.06.2025